Modelagem de uma curva diária equivalente anual de geração fotovoltaica aplicando em um cenário - Cezar, Cleberton Londero (2019)
In this study there will be presented an evaluation methodology and scaling of a photovoltaic system with credit compensation. For the validation of the data the computational tool Radiosol 2 was used for the scenery of a feed factory from the city of Santa Maria – RS that has a monthly energy consumption of 5.807kWh. One of the results of this study was a daily equivalent curve of annual photovoltaic generation for different methodologies, as well as the creation of a flowchart for the elaboration of the daily equivalent curve that is a merity figure of the electric energy generated by the annual representative system. The projected system presents the estimative that attends around 100% of the factory consumption. In this dissertation there will be presented an analysis of the energetic gain between different configurations of the angle of inclination variation for the city of Santa Maria – RS, generating a study and a daily equivalent curve of annual photovoltaic energy generation for the proposal of inclination and comparing them. There was also done the study of economic viability for its application, searching to identify the most viable.